Transformation of Electricity Supply Industry in Malaysia An Overview - Falil, Nor Farhana; Nasir, Nurul Fitriah (Research Progress in Mechanical and Manufacturing Engineering, 2021)
The global trend in the electricity market has driven Malaysia to restructure its industry to be more dependable, open, competitive, and long-term. Furthermore, vertically integrated entities' centralized power purchasing units have been chastised for failing to provide a level playing field for generation sector players vying to sell power to a single buyer. This paper attempts to study the evolution of the Malaysian Electricity Supply Industry (MESI), which has gone through several stages of change, evolving from a largely single entity to a multi-player industry, especially in the generation field. This case study covered electricity market in Malaysia. Electricity Market model also discusses and introduced a number of electricity market model that is designed to be suited with its local condition through evolvement and transition of the Electricity Supply Industry (ESI). Besides that, Renewable Energy Market in the Malaysian context is also discussed.